Implementation of The Collaborative Funding Model for Sheep Fattening Farming at The Riungmukti Multipurpose Cooperative Kalapanunggal District, Sukabumi Regency, West Java - Kuswaryan, Sondi; Firmansyah, Cecep; Daud, Andre Rivianda; Sulistyati, Marina (Jurnal Pengabdian Masyarakat Biologi dan Sains, 2023)
Sheep farming is an important income for rural communities. The fattening segment has better business prospects than breeding. This conducive business opportunity cannot be accessed bysheep farmerss, due to limited financial capital for purchasing fattening sheep. Community service activities aimed to provide funds to finance fattening by sheep farmers, using a crowdfunding system. Implementation of activities using the territorial mapping method, counseling and assistance to members and administrators of the Riungmukti Multipurpose Cooperative, Kalapanunggal District, Sukabumi, West Java. The program evaluation showed that crowdfunding system by strengthening the Ecobis 2-3-5 profit sharing pattern received appreciation from the majority of sheep farmers and investors. The Ecobis 2-3-5 pattern provides financial feasibility for investors, with a rate of return on investment value added of 11.42 percent/year, greater than interest on bank savings, deposits and interest on people's business credit loans (KUR). Cooperative program operational costs can be covered, as well as increasing employment and business opportunities for farmers. Increasing program performance can be done through investment promotions to attract investors, improving services to farmers, especially the movement to plant forage on empty and/or unproductive land with the addition of legume plants. It is necessary to run monthly communication forums between farmers for business motivation, exchange experiences, and increase the capacity for adopting science and technology.